Cyclic AMP Sensor EPAC Proteins and Their Role in Cardiovascular Function and Disease. Issue 5 (4th March 2016) - Lezoualc'h, Frank; Fazal, Loubina; Laudette, Marion; Conte, Caroline
Abstract : cAMP is a universal second messenger that plays central roles in cardiovascular regulation influencing gene expression, cell morphology, and function. A crucial step toward a better understanding of cAMP signaling came 18 years ago with the discovery of the exchange protein directly activated by cAMP (EPAC). The 2 EPAC isoforms, EPAC1 and EPAC2, are guanine-nucleotide exchange factors for the Ras-like GTPases, Rap1 and Rap2, which they activate independently of the classical effector of cAMP, protein kinase A. With the development of EPAC pharmacological modulators, many reports in the literature have demonstrated the critical role of EPAC in the regulation of various cAMP-dependent cardiovascular functions, such as calcium handling and vascular tone. EPAC proteins are coupled to a multitude of effectors into distinct subcellular compartments because of their multidomain architecture. These novel cAMP sensors are not only at the crossroads of different physiological processes but also may represent attractive therapeutic targets for the treatment of several cardiovascular disorders, including cardiac arrhythmia and heart failure.